Urnal of Agriculture Food and Environment (2005)
The study explored the impacts of Civil Crises in Plateau State on Wase Wildlife Park (WWLP), Nigeria. Data for the study were obtained through observations, interviews and structured questionnaires. Data obtained were analysed using descriptive statistics. Results revealed that Religion (62.5%), Politics (45.0%) and Tribalism (75.5%) were the causes of the crises. All the respondents indicated that the crises affected tourism; economically (72.5%) and politically (27.5%). Due to the crises most indigenes (92.5%) of Wase Local Government Council ran away. All the staff of WWLP escaped for safety and later were reposted to other parks in Plateau State by the Plateau State Tourism Corporation. WWLP was abandoned and forgotten with all the animal species exposed to the danger of being poached. Park facilities were looted (92.5%) and vandalized (5.0%). Wildlife resources including endangered species were threatened and wasted with tourism hampered. Annual revenue generation of WWLP through tourism declined from N294, 792.0 in the year 2001 to zero. Wase remains deserted. It is expedient that the Plateau State Government looks into the root causes of conflicts in the State to ensure that a long lasting solution is found as ecotourism cannot thrive where there is crises